Breaking News of Cancer Diagnosis: A Qualitative Study on the Experiences and Emotional Needs of Patients With Cancer in a Multiethnic Asian Setting. Issue 4 (April 2021) - Wong, Li-Ping; Kong, Yek-Ching; Bhoo-Pathy, Nanthini Thevi; Subramaniam, Shridevi; Bustamam, Ros Suzanna; Taib, Nur Aishah; Ho, Gwo-Fuang; Zaharah, Hafizah; Mellor, Matin; Woo, Yin-Ling; Yip, Cheng-Har; Bhoo-Pathy, Nirmala
Abstract : PURPOSE: The breaking of news of a cancer diagnosis is an important milestone in a patient's cancer journey. We explored the emotional experiences of patients with cancer during the breaking of news of a cancer diagnosis and the arising needs in a multiethnic Asian setting with limited supportive cancer care services. METHODS: Twenty focus group discussions were conducted with 102 Asian patients with cancer from diverse sociodemographic backgrounds. Thematic analysis was performed. RESULTS: While most participants, especially younger patients with young children, experienced intense emotional distress upon receiving a cancer diagnosis, those with a family history of cancer were relatively calm and resigned. Nonetheless, the prior negative experience with cancer in the family made affected participants with a family history less eager to seek cancer treatment and less hopeful for a cure. Although a majority viewed the presence of family members during the breaking of bad news as important, a minority opted to face it alone to lessen the emotional impact on their family members. Difficulties disclosing the news of a cancer diagnosis to loved ones also emerged as an important need. Sensitive and empathetic patient-physician communication during the breaking of news of a cancer diagnosis was stressed as paramount. CONCLUSION: A patient-centered communication approach needs to be developed to reduce the emotional distress to patients and their families after the breaking of bad news of a cancer diagnosis. This is expected to positively affect the patients' subsequent coping skills and attitudes toward cancer, which may improve adherence to cancer therapy.